Osteonecrosis in Systemic Lupus Erythematosus: An Early, Frequent, and Not Always Symptomatic Complication. (5th August 2012) - Caramaschi, Paola; Biasi, Domenico; Dal Forno, Ilaria; Adami, Silvano
Abstract : Osteonecrosis may complicate the course of systemic lupus erythematosus and may contemporaneously affect multiple joints. The major risk factor associated with the development of osteonecrosis is the use of glucocorticoid at high doses. Recent studies using serial MRI, which represents the "gold standard" for the early detection of osteonecrosis, yielded some interesting findings about the natural history of this clinical entity. Osteonecrosis in the majority of the cases is asymptomatic and occurs early in the course of the disease. Its later occurrence is associated with lupus flare that requires the increase of corticosteroid dose. The optimal treatment of osteonecrosis is controversial. In case of silent osteonecrosis involving a small area conservative strategy is usually adequate. When lesions are symptomatic surgical treatment as core decompression or free vascularized fibular grafting is required; extracorporeal shockwave treatment may represent an alternative therapeutic approach. When the lesion has a medium-large dimension or involves a weight-bearing area bone collapse is a common complication requiring total joint replacement. Coadministration of bisphosphonate or warfarin with high doses of corticosteroid might be a promising preventive strategy of osteonecrosis.